Echolocation click parameters and biosonar behaviour of the dwarf sperm whale ( Kogia sima ) - Malinka, Chloe E; Tønnesen, Pernille; Dunn, Charlotte A; Claridge, Diane E; Gridley, Tess; Elwen, Simon H; Teglberg Madsen, Peter (Journal of Experimental Biology, 2021)
Dwarf sperm whales ( Kogia sima ) are small toothed whales that produce narrow-band high-frequency (NBHF) echolocation clicks. Such NBHF clicks, subject to high levels of acoustic absorption, are usually produced by small, shallow-diving odontocetes, such as porpoises, in keeping with their short-range echolocation and fast click rates. Here, we sought to address the problem of how the little-studied and deep-diving Kogia can hunt with NBHF clicks in the deep sea. Specifically, we tested the hypotheses that Kogia produce NBHF clicks with longer inter-click intervals (ICIs), higher directionality and higher source levels (SLs) compared with other NBHF species. We did this by deploying an autonomous deep-water vertical hydrophone array in the Bahamas, where no other NBHF species are present, and by taking opportunistic recordings of a close-range Kogia sima in a South African harbour. Parameters from on-axis clicks (n=46) in the deep revealed very narrow-band clicks (root mean squared bandwidth, BW RMS , of 3±1 kHz), with SLs of up to 197 dB re. 1 µPa peak-to-peak (μPa pp ) at 1 m, and a half-power beamwidth of 8.8 deg. Their ICIs (mode of 245 ms) were much longer than those of porpoises (<100 ms), suggesting an inspection range that is longer than detection ranges of single prey, perhaps to facilitate auditory streaming of a complex echo scene. On-axis clicks in the shallow harbour (n=870) had ICIs and SLs in keeping with source parameters of other NBHF cetaceans. Thus, in the deep, dwarf sperm whales use a directional, but short-range echolocation system with moderate SLs, suggesting a reliable mesopelagic prey habitat.